(untitled) (Communications in Computational Physics, 2021)
Recently, there is a need for a general-purpose event generator for decays of an elementary particle or a hadron to a state of higher multiplicity (N ≥ 2) that is simple to use and universal. We present the structure of such a library for preparation of generators that generate kinematics of decay processes and can be used to integrate any matrix element squared over phase space of this decay. Some test examples are presented, and results are compared with results known from the literature. As one of examples we consider the Standard Model Higgs boson decay into four leptons. The generators discussed here are compatible with the ROOT interface.